The Role of Green Energy Technologies Development, Carbon Finance, Carbon Tax and Economic Growth on Environmental Conditions in ASEAN Countries - Yunikewaty Yunikewaty; Dwi Siswahyudi (International Journal of Energy Economics and Policy, 2023)
Green technology and carbon finance have the potential to greatly add significance towards traditional financing practices related to carbon emissions because of information based nature, Thus, exploration of green technologies and carbon finance assist economies in the formulation of effective policies. By employing the panel data of ASEAN economies from 2011-2019, the study used CUP-FM and CUP-BC methods to empirically analyze the said relationship. The outcomes of the study revealed that green technologies, carbon finance, carbon taxes, economic growth decrease GHG emissions. It implies that the synergetic effect of green technologies, carbon finance, carbon tax and economic growth play an essential role in improving environmental conditions. Consequently, ASEAN region can reshape the policies by integrating green technologies and carbon finance and also looks into country’s local condition to improve the urban environmental efficiency, hence, achieving carbon neutralization goal.